What left and right means to Portuguese citizens - Freire, André; Belchior, Ana Maria (Comparative European Politics, 2011)
Although previous studies have concluded that, in comparative terms, Portuguese citizens exhibit low levels of social, value and partisan left-right attitude anchoring, the truth is that the items used in these studies are rather limited. Moreover, the meaning attributed by voters to each ideological camp was never studied. This study seeks to overcome these limitations. The article reiterates that in a comparative perspective, Portugal does exhibit low levels of left-right attitude anchoring. This is the point of departure of the article and also, it is argued, a good reason to try to further understand this case and extract from it inferences about similar cases. One of this study's major findings is that the meanings attributed to the left-right divide are not clear and structured; moreover, this lack of clarity is positively correlated with low levels of media exposure, education and left-right self-placement. Although the article tests hypotheses about how different groups (manual workers versus other social classes; older versus younger cohorts; post-materialists versus other value groups) might give different meanings to the left-right divide, the major finding is that media exposure and education are in any case the crucial factors explaining the more or less structured meanings for ideological conflicts.